Results of Using a “2-in-1” Single-Stage Revision Total Knee Arthroplasty for Infection with Associated Bone Loss: Prospective 2-Year Follow-Up - Holland, George; Brown, Gavin; Goudie, Stuart; Brenkel, Ivan; Walmsley, Philip J. (The Journal of Knee Surgery, 2019)
Prosthetic joint infections provide a complex challenge for management, owing to their often difficult diagnoses, need for multiple surgeries, and increased technical and financial requirements. The ‘2 in 1’ single-stage approaches have been recently advocated in the field of arthroplasty on account of their reduction in risks, costs, and complications. The aim of our study was to investigate the outcomes of this variant of single-stage revision, which is used in the setting of infection following primary total knee replacement (TKR) and associated bone loss. Prospective data were collected from all patients presenting with an infection following primary TKR over an 8-year period (2009–2017). We examined revision procedures that were undertaken as a single-stage procedure and had bone loss present. Patients were followed-up for evidence of recurrent infection. Functional assessments were conducted using range of motion, Oxford Knee Score (OKS), American Knee Society Score (AKSS), and Short Form-12 (SF-12) survey. Twenty-six patients were included in the analysis, two of whom had previously failed 2 stage revision; another three among them had failed debridement, antibiotics, irrigation, and implant retention procedures. The mean age was 72.5 years, mean body mass index was 33.4, and median American Society of Anesthesiologists (ASA) physical status classification was 2. The mean time to revision was 3.5 years (3 months to 12 years). Six patients had actively been discharging sinuses at the time of surgery. Only 4/26 patients possessed no positive microbiological cultures from deep tissue samples or joint aspirates. One patient was afflicted with a recurrence of infection. This patient did not require further surgery and was successfully treated with the help of long-term antibiotic suppression. There were statistically significant improvements in both the pain component of AKSS scores (preoperative 4.3 to postoperative 32.4) and the functional component of AKSS scores (preoperative 10.7 to postoperative 15.7). There was no significant improvement in flexion; however, mean extension (increased from 18.5 to 6.9 postoperative) and total range of motion (increased from 69.2 preoperative to 90.3 postoperative) both showed statistically significant improvements. The use of “2-in-1” single-stage revision can be considered as an effective option for treating infection following TKR and associated bone loss.
Keywords: arthroplasty; revision; infection